2021
DOI: 10.1186/s40623-020-01335-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Na layer and CNA variations observed at Syowa, Antarctic

Abstract: We have performed a statistical data analysis on relationship between simultaneous Na density data and cosmic noise absorption (CNA) data, which is an indicator for energetic particle precipitation, obtained at Syowa, Antarctic in 2000–2002. It is found that the Na densities around the topside of Na layers (above $$\sim 95 \,\hbox {km}$$ ∼ 95 km height) tended to be smaller wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Energetic electrons precipitating into the ionosphere collide with neutral gas and contribute to various ionospheric phenomena, such as auroral emissions, electron density enhancement, and cosmic noise absorption [e.g., Tao et al, 2020;Oigawa et al, 2021;Tsuda et al, 2021]. The temporal and spatial scales of electron precipitation are controlled by processes occurring in the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Energetic electrons precipitating into the ionosphere collide with neutral gas and contribute to various ionospheric phenomena, such as auroral emissions, electron density enhancement, and cosmic noise absorption [e.g., Tao et al, 2020;Oigawa et al, 2021;Tsuda et al, 2021]. The temporal and spatial scales of electron precipitation are controlled by processes occurring in the magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Oka et al (2021) analyzed an unusual short-duration SEP event and found that the higher-energy (> 30 MeV) protons were detected about four hours after the shock arrival of ICME. The impact of energetic particle precipitation on atmospheric chemistry was investigated by Tsuda et al (2021) and they found that the Na loss around the topside of Na layer would be induced by the energetic particle precipitation.…”
mentioning
confidence: 99%